The Effect Of Tui Na Massage On Eating Difficulties In Toddlers In The Working Area Of The Rambah Hilir Ii Community Health Center, Rokan Hulu Regency - Rika Herawati; Siti Nurkhasanah; Eka Yuli Handayani; Siti Nurpadinah (CV. AFDIFAL MAJU BERKAH, 2025)
Based on a preliminary survey conducted by researchers on toddlers in the Rambah Hilir II Health Center Working Area of Rokan Hulu Regency, there were 10 toddlers who had difficulty eating. Difficulty eating causes several eating problems that often arise, including: fussiness, vomiting, being too picky, eating phobia, eating slowly, and refusing food. Eating difficulties can be treated with non-pharmacological treatment, namely Tui Na Massage. This massage can improve blood circulation in the spleen and digestion. This method uses pressure on the body's meridian points or energy flow lines, so that appetite will increase. The purpose of this study was to determine the effect of Tui Na Massage on eating difficulties in toddlers in the Rambah Hilir II Health Center Working Area, Rokan Hulu Regency. This type of research is quantitative research with a Pre-Experimental research design without a control group using the one-group Pretest and posttest approach. The sample in the study consisted of 10 respondents. The average value of respondents' eating difficulties before and after Tui Na Massage was 1,400 with a standard deviation of 0.240 and a standard error of 0.076, with the results of the T dependent test obtained p value = 0.000 <0.05; this means p value <0.05. So it can be concluded that there is an effect of Tui Na Massage on eating difficulties in toddlers in the Working Area of Rambah Hilir II Health Center, Rokan Hulu Regency. It is expected that after the research is conducted, the respondent parents can increase their knowledge about Tui Na Massage and its massage techniques to help overcome eating difficulties in toddlers with non-pharmacological treatment.